Low Altruism as a Cause of Ostracism - Huang, Lianqiong; Zhu, Yingge; Zhang, Denghao (Frontiers in Psychology, 2021)
This study focused on the causes of ostracism and explored the relationship between altruistic personality traits and ostracism. Using a combination of questionnaire surveys and laboratory experiments, results showed that: altruism was one reason why individuals suffer from ostracism (Study 1), and individuals with lower altruism were more vulnerable to be ostracized than those with higher altruism. The relationship between altruism and ostracism was partially mediated by social responsibility (Study 3). When facing a low-altruistic target, the source would infer that the social responsibility level of this target was also low, thereby leading the ostracism intention to the target. Empathy did not moderate the relationship between altruism and ostracism. On the one hand, empathy did not moderate the direct effect of altruism on ostracism (Study 2); on the other hand, it also did not moderate the mediating role of social responsibility (Study 3). The strengths and limitations of this research are also discussed.